Distance learning in the system of higher education in Kazakhstan (based on main platforms and services) - I.S. Kalymanov (Počki, 2022)
In this article, the author considers distance learning as a new stage in the development of education. The author focuses on the latest achievements in the educational process, as well as the impact of the self-isolation process on the introduction of distance learning. The main advantages and disadvantages of distance learning technology are determined. The basic principles that a teacher needs to master for conducting distance learning of students are considered. The main educational platforms and services are presented, such as Microsoft Teams, Moodle, Zoom, Cisco Webex, Google Classroom. The main features of each platform and service for distance learning are highlighted. The strengths and weaknesses of each of the above platforms and services are considered.